2017
DOI: 10.1530/eje-16-0945
|View full text |Cite
|
Sign up to set email alerts
|

Distinct inflammatory gene expression in extraocular muscle and fat from patients with Graves’ orbitopathy

Abstract: Tissues involved in GO exhibited different mRNA levels of and. Gene expression in OF was similar for TED patients and controls. , and mRNA levels were higher in TED EOM than those in control EOM. was disproportionally elevated compared with; this finding was indicative of a local proinflammatory profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
1
7
1
1
Order By: Relevance
“…While our data revealed several differentially expressed gene profiles between diseased and control patients, we found that genes related to developmental morphogenesis and lineage commitment were predominantly dysregulated in TAO. Unlike previous gene expression profiling studies that analyzed orbital fat pads and extraocular muscle, 17 , 38 , 44 the current study did not detect any significant different expression in genes related to inflammation (RNAseq dataset, Table 2 ). These findings suggest that our data may reveal the intrinsic cellular characteristics of the stem cell niche that are otherwise masked by the massive immunogenic response in the tissue from TAO patients.…”
Section: Discussioncontrasting
confidence: 93%
“…While our data revealed several differentially expressed gene profiles between diseased and control patients, we found that genes related to developmental morphogenesis and lineage commitment were predominantly dysregulated in TAO. Unlike previous gene expression profiling studies that analyzed orbital fat pads and extraocular muscle, 17 , 38 , 44 the current study did not detect any significant different expression in genes related to inflammation (RNAseq dataset, Table 2 ). These findings suggest that our data may reveal the intrinsic cellular characteristics of the stem cell niche that are otherwise masked by the massive immunogenic response in the tissue from TAO patients.…”
Section: Discussioncontrasting
confidence: 93%
“…As Table 3 shows, the expression of IL-1, IL-6, IL-8, IL-10, IL-17, IFN-γ, and TNF-α was significantly upregulated in EOMs from GO patients. Cytokines such as IL-6, IFN-γ and TNF-α were previously reported to promote fibroblast proliferation and differentiation in GO [17]. More importantly, we found by KEGG analysis of the biological pathways that 12 of 19 pathways were involved in immune and inflammatory responses.…”
Section: Discussionmentioning
confidence: 55%
“…Inflammation in the orbit of patients with GO is accepted to be caused by autoimmune responses and inflammatory cytokine release [17,18]. RNA methylation has been reported to regulate T-cell homeostasis and the inflammatory response by targeting inflammatory pathways [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ряд а второв пола га ют, что истинная рефрактерность -геномная. То есть одной из основных причин снижения чувствительности к ГК, отсутствия эффекта от их применения является генетическая вариабельность, в том числе полиморфизм на уровне глюкокортикоидного рецептора (ГКР) NR3C1 [9,10]. Целью настоящего исследования стало выявление у больных ЭОП взаимосвязи между полиморфизмом гена ГКР NR3C1 и ответом на терапию ГК.…”
Section: эффективная фармакотерапия 33/2019unclassified